Efektivitas Pembelajaran Mengenal Lambang Bilangan Melalui Media Setir Angka pada Kelompok A di Taman Asuh Anak Muslim X - Mila Karmila; Asep Dudi Suhardini (UNISBA Press, 2021)
Abstract. This research is motivated by cognitive abilities, namely recognizing the number symbols in group A children, which are still low. This is due to the fact that they rarely use interesting learning media, because they more often use student worksheets (LKS) or lecture methods so that children are less interested in the learning process to recognize numbers symbols. The purpose of this study was to improve the ability to recognize 1-10 number symbols in children before and after using the numbering wheel media and also to determine the effect of the numbering wheel media on the ability to recognize 1-10 number symbols. The method used in this study is a quasi experimental type One-Group Pretest-Posttest Design with a quantitative approach. The population and sample of this study were 12 group A children. The data collection method used was observation and documentation. Data analysis, before the treatment was carried out using the numbering wheel media the ability to recognize the symbol said the child was still low.. the score result of data obtained from studied before using the media numbering wheels are 210 (54,69%) and after using media numbering wheel scores are 344 (68,58%) there was significantly increased in scores about 143 (34,89%). The paired t test results of the pretest and posttest results were significant because they had a value of p <0.05 (p = 0.000 <0.05) meaning that Ho was acceptable, ie there was an increase in recognizing the symbol numbers of group A children. The conclusions showed that the numbering wheel was effective to increase the ability to recognize symbols numbers in group A children in TAAM X. Abstrak. Penelitian ini dilatar belakangi oleh kemampuan kognitif yaitu mengenal lambang bilangan pada anak kelompok A, yang masih rendah. Hal ini dikarnakan jarangnya menggunakan media pembelajaran yang menarik, karna lebih sering menggunakan lembar kerja siswa (LKS) atau metode ceramah sehingga anak kurang tertarik dalam proses pembelajaran mengenal lambang bilangan. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan mengenal lambang bilangan 1-10 pada anak sebelum dan sesudah menggunakan media setir angka dan juga untuk mengetahui pengaruh media setir angka terhadap kemampuan mengenal lambang bilangan 1-10. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen jenis One –Group Pretest-Posttest Design dengan pendekatan kuantitatif. Populasi dan sempel penelitian ini adalah 12 anak kelompok A. Metode pengumpulan data yang digunakan adalah observasi serta dokumentasi. Analisis data, sebelum dilaksanakan perlakuan menggunakan media setir angka kemampuan mengenal lambang bilang anak masih rendah. Data yang diperoleh dari hasil penelitian sebelum menggunakan media setir angka, mendapat skor 210(54,69%) dan sesudah menggunakan media setir angka mendapat skor 344 (89,58%) maka terlihat peningkatan skor sebanyak 143 (34,89%). Tampak hasil uji t berpasangan hasil pretest dan posttest signifikan karna memiliki nilai p < 0.05 (p = 0,000 < 0.05) artinya Ho dapat diterima, yaitu terdapat peningkatan mengenal lambang bilangan anak kelompok A. Kesimpulan menunjukan bahwa permainan setir angka efektif untuk meningkatkan kemampuan mengenal lambang bilangan pada anak kelompok A di TAAM X.